Disarming the skeptical puzzle: an epistemology of defense contrastivist - Luis Fernando dos Santos Souza (2016)
This thesis aims facing the skeptical argument classic type from the contrastivist knowledge theory. The problem we will approach is when we accept the epistemic logic principle called closing principle. The principle states that knowledge is closed under implication and seems to regulate the way we expand our ordinary knowledge. Basically the closure affirms that for every epistemic subject S, target proposition p and logic Contrary q, If S knows that p and S knows that p logically implies q, so S knows that q. The problem arises when the contrary logic is a skeptical hypothesis, a hypothesis we can't know. Operating a modus tollens in the beginning closure a skeptic concludes logically that we can't know anything. To contextualize the skeptical problem contrastive solution problem that makes uses of closing we will show two theories treatment that will serve as preliminaries. The first is Fred Dretske's Relevant Alternatives Theory and the secondd is David Lewis' Contextualism. Dretske acknowledged accepting closure means surrendering to skepticism, for this reason tried to solve the problem rejecting the closing validity. The Closure rejection by Dretske, however, was considered ad hoc, therefore, unable to solve the problem. David Lewis contextualist solution, however, accepts the closure principle validity and seeks problem resolution by accusing the skeptic of misunderstand as to semantic term know. For Lewis, "knowledge" is an indexical term and , as such, undergoes contextual (semantic and epistemic) variations. Understand adequately the knowledge indexicality, for the contextualist, will show the paradox is only apparent. We will show Lewis theory advantages, but we will also show that it is unsatisfactory to solve skepticism problem. We will defend, finally, that the theory that best accommodates ordinary knowledge against skeptical arguments is Jonathan Schaffer's Contrastivism. The contrastivist theory will look to dodge the problem appealing to an epistemic revisionism. For Schaffer, the knowledge relation is essentially ternary and when we look at the skeptic puzzle by contrastivist bias we will perceive the problem is mitigated, that is, it is weakened in a most intuitive way than Dretske and Lewis theories. The contrastivist theory will defend, in an innovative way, that ordinary knowledge is compatible with skeptical doubt.